The effect of spinal curvature on the photogrammetric assessment on static balance in elderly women - Drzał-Grabiec, Justyna (BioMed Central, 2014)
BACKGROUND: Involutional changes to the body in elderly patients affect the shape of the spine and the activity of postural muscles. The purpose of this study was to assess the influence of age-related changes in spinal curvature on postural balance in elderly women. METHODS: The study population consisted of 90 women, with a mean age of 70 ± 8.01 years. Static balance assessments were conducted on a tensometric platform, and posturographic assessments of body posture were performed using a photogrammetric method based on the Projection Moiré method. RESULTS: The results obtained were analysed using the Spearman’s rank correlation coefficient test. We found a statistically significant correlation between body posture and the quality of the balance system response based on the corrective function of the visual system. The shape of the spinal curvature influenced postural stability, as measured by static posturography. Improvement in the quality of the balance system response depended on corrective information from the visual system and proprioceptive information from the paraspinal muscles. CONCLUSIONS: The sensitivity of the balance system to the change of centre of pressure location was influenced by the direction of the change in rotation of the shoulder girdle and spine. Development of spinal curvature in the sagittal plane and maintenance of symmetry in the coronal and transverse planes are essential for correct balance control, which in turn is essential for the development of a properly proportioned locomotor system.